A Literature Analysis of Consumer Privacy Protection in Augmented Reality Applications in Creative and Cultural Industries: A Text Mining Study - Kang, Yowei; Su, Yu-Sheng (Frontiers in Psychology, 2022)
Digital reality technologies (such as A.R., V.R., and M.R.) have recently become a key component of promoting creative and cultural industries (CCIs) worldwide to transform static cultural heritage exhibits into more engaging, entertaining, and immersive experiences. These technologies present an exciting example of studying how cross-national consumers would respond to the potential invasion of privacy of these technologies, despite their interactivity, realism, and visualization. This literature review study mainly focuses on one essential branch of the creative and cultural industry: museums and their applications of digital reality technologies. Because many of these location-based A.R. applications by museums are inherently sensitive to users' locational information, there is also a rising concern of the potential infringement of personal privacy. A thorough examination of existing literature on how cross-cultural consumers respond to privacy concerns related to the museum's A.R. applications will help uncover how scholars have approached and studied these crucial issues. Unlike traditional literature review analyses, we employed a text mining of retrieved 715 studies articles from Business Source Complete and Engineering Village (E.I.) databases. Our study found that privacy and user(s) /visitor(s) has dramatically increased since 2017. Extracted vital phrases, such as Security and Privacy, Privacy Concerns, and Privacy Protection, have emerged in the literature in response to museums' rapid implementation of augmented technology. Discussions and implications are provided.